Cebrián Abellán, F. y Panadero Moya, M. (coord.) (2013). Ciudades medias. Formas de expansión urbana - Vázquez Varela, Carmen (Documents d'Anàlisi Geogràfica, 2013)
Cebrián Abellán, F. y Panadero Moya, M. (coord.) (2013) Ciudades medias. Formas de expansión urbana Madrid: Biblioteca Nueva, 284 p. ISBN: 978-84-9940-594-0